Sustainability and the problem of consumption - Ulrich Witt (Max Planck Institute of Economics, 2011)
Strong growth in disposable income has inflated consumption to unprecedented, but not sustainable levels. In this process consumer behavior has been changing. To explain the driving forces of this development, the paper introduces a theory of evolving consumer preferences that is molded in an evolutionary paradigm. The theory allows to better assess how individual welfare would be directly affected by policy measures designed to make consumption sustainable. Such policy measures are likely to also trigger indirect welfare losses by negative employment effects. The policy debate therefore needs to pay attention to both direct and indirect welfare effects. As a concrete proposal a redesign of consumption taxes is discussed that accounts for both concerns.
Keywords: A13; D01; D03; D11; D62; H23; H24; Q01; Q38; 330; consumption; preferences; growth; sustainability; satiation; welfare; consumption tax; Nachhaltige Entwicklung; Konsumentenverhalten; Präferenztheorie; Evolutionsökonomik; Verbrauchsteuer; Wohlfahrtseffekt; Theorie